1991
DOI: 10.1093/sjaf/15.3.125
|View full text |Cite
|
Sign up to set email alerts
|

Economic Comparison of Natural and Planted Regeneration of Loblolly Pine

Abstract: The need for low cost, ecologically sound, pine regeneration alternatives for adoption on Non-Industrial Private Forest (NIPF) lands is urgent. Seed tree and shelterwood methods of loblolly pine regeneration were examined by profitability analysis. Each were shown to be good investments. Also, a profitability comparison was made between natural regeneration and planted stands. Natural loblolly regeneration is financially competitive with clearcut and plant silviculture. The internal rate of return (IRR) was 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Our results also indicate that short-rotation planted pines are slightly preferred using LEV at sufficiently low discount rates, with higher net present values than natural stands. Third, the limited prior research on forests in the U.S. South found similar results, with natural forest investments having higher IRRs than planted forests (Cubbage et al 1991;Dangerfield and Edwards 1991). Fourth, the direction of the comparative results we found would remain the same as long as relative input costs were the same for planted or natural stands, assuming timber prices were constant.…”
Section: Wwwforest-journalcomsupporting
confidence: 61%
See 1 more Smart Citation
“…Our results also indicate that short-rotation planted pines are slightly preferred using LEV at sufficiently low discount rates, with higher net present values than natural stands. Third, the limited prior research on forests in the U.S. South found similar results, with natural forest investments having higher IRRs than planted forests (Cubbage et al 1991;Dangerfield and Edwards 1991). Fourth, the direction of the comparative results we found would remain the same as long as relative input costs were the same for planted or natural stands, assuming timber prices were constant.…”
Section: Wwwforest-journalcomsupporting
confidence: 61%
“…In the United States, Dangerfield and Edwards (1991) compared the profitability between natural regeneration and planted stands of loblolly pine (Pinus taeda). It was found that natural loblolly regeneration was financially competitive with a clearcut-and-plant method.…”
Section: Introductionmentioning
confidence: 99%
“…Given the limited investment capital available to many nonindustrial private owners, it is important to consider new research on alternatives to highly intensive management practices. This point is especially significant in light of findings that natural regeneration has the potential to yield a higher internal rate of return on investment than planting, 10.8 percent versus 10.1 percent (Dangerfield and Edwards 1991). Current research covering low-cost regeneration techniques for pine-site timberland offers promise (Edwards and Dangerfield 19901, as do inexpensive management treatments for rapid recovery of understocked pine stands (Baker 1989).…”
Section: Discussionmentioning
confidence: 99%
“…An economic comparison was made by Dangerfield & Edwards(1991) between natural and planted regeneration of Loblolly pine under deterministic case. They found that natural loblolly regeneration is financially competitive with planted regeneration.…”
Section: Introductionmentioning
confidence: 99%